egenerative joint disease in the skeletal remains of a captive Bornean sun bear (Helarctos malayanus euryspilus) - Awang-Junaidi, Awang Hazmi; Nie, Yeoh Boon; Wong, Siew Te; Sarkawi, Nur Nabila; Khairul Anuar, Wafeq Mu’Izzadin; Zainal Ariffin, Siti Mariam (ResearchersLinks Ltd, 2024)
The Bornean sun bear (Helarctos malayanus euryspilus) is recognized as the smallest bear species globally and is vulnerable to degenerative joint disease (DJD). This study presents the results of a detailed examination of the skeleton remains of one adult male captive Bornean sun bear obtained from the Bornean Sun Bear Conservation Centre (BSBCC), Sandakan, Sabah, Malaysia, specifically for DJD lesions. The examination revealed osteoarthritis in multiple sites of the appendicular joint, including the hip joint, stifle joint, elbow joint, and carpal joint, with bilateral involvement. Spondylosis deformans was observed in the cervical and thoracic vertebrae. The DJD changes include osteophyte formation, subchondral bone degradation, and joint remodelling. In conclusion, the findings provide valuable insights into the joint health of Bornean sun bear and highlight the importance of proactive measures to mitigate factors contributing to joint degeneration, such as optimizing husbandry practices and providing appropriate environmental enrichment.